1995
DOI: 10.1128/mcb.15.3.1554
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activators Differ in Their Responses to Overexpression of TATA-Box-Binding Protein

Abstract: We investigated how overexpression of human TATA-box-binding protein (TBP) affects the action of estrogen receptor (ER) and compared the response with that of other activators. When ER activates a simple promoter, consisting of a response element and either the collagenase or tk TATA box, TBP overexpression potentiates transcription. TBP potentiates only estrogen-induced and not basal transcription and does so independent of spacing between response element and TATA box. TBP overexpression also reduces autoinh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 58 publications
7
96
0
3
Order By: Relevance
“…Our results would be consistent with the incorporation of hTAF II 28 and TBP spm3 into a TFIID complex comprising endogenous TAF II s. Indeed, we and others have previously shown that a fraction of transfected TBP spm3 and hTAF II 28 (and indeed other TAF II s) do associate with the endogenous cellular TFIID (12,22,32). Transfected hTAF II 28 may be assembled into TFIID complexes via TAF-TAF rather than TAF-TBP interactions, explaining why the mutations in TBP do not abolish functional cooperation.…”
Section: Discussionsupporting
confidence: 78%
“…Our results would be consistent with the incorporation of hTAF II 28 and TBP spm3 into a TFIID complex comprising endogenous TAF II s. Indeed, we and others have previously shown that a fraction of transfected TBP spm3 and hTAF II 28 (and indeed other TAF II s) do associate with the endogenous cellular TFIID (12,22,32). Transfected hTAF II 28 may be assembled into TFIID complexes via TAF-TAF rather than TAF-TBP interactions, explaining why the mutations in TBP do not abolish functional cooperation.…”
Section: Discussionsupporting
confidence: 78%
“…Because transcriptional activation by the ER occurs with chromatin but not with nonchromatin templates, we suggest that chromatin provides an environment that is conducive to multiple cycles of transcription, such as that mediated by the ER. It has also been found that ER interacts with TBP, hTAF II 30, hTAF II 28, and TFIIB (Ing et al 1992;Jacq et al 1994;Sadovsky et al 1995;Beato and Sá nchez-Pacheo 1996;May et al 1996). Thus, the results collectively suggest that there might be a complex containing ER and TFIID and/or TFIIB that remains bound at the promoter for multiple cycles of transcription and facilitates reinitiation.…”
Section: Er Promotes Transcription Reinitiation With Chromatin Templatessupporting
confidence: 48%
“…Recently, it has been reported that several SRs can interact directly with components of the basal transcription machinery, such as TBP (11), TFIIB (12), TFIIF (13), and TFIIH (14). In addition, specific sets of proteins are recruited by the SRs as coregulators that may function as bridging factors between the receptors and general transcription machinery in the preinitiation complex (15,16).…”
mentioning
confidence: 99%